Tick infestation (Acari ixodidae) of apodemus flavicollis melchior, 1834 (Rodentia: muridae) in Vojvodina, Serbia - Petrović Aleksandra (Proceedings of the International Symposium on Analytical and Environmental Problems, 2017)
The vector potential of rodents as hosts of mainly larval and nymphal stages of ixodid ticks is influenced by a large number of factors. Considering the confirmed role of mice as important reservoirs and vectors of zoonotic diseases, the aim of the study was to determine the qualitative and the quantitative diversity of ectoparasiting ticks. The total number of trapped mice was 238, and the total number of collected ticks was 449. Six species from four genera of ixodid ticks were identified: Ixodes ricinus, I. trianguliceps, Dermacentor marginatus, Haemaphysalis concinna, H. punctata and Rhipicephalus sanguineus. The average number of ticks per mouse was 2.211823±0.157862. The highest values for the selected parameters were: the prevalence for I. ricinus larvae (8.241%), the average infestation intensity for D. marginatus larvae (4.714), the abundance and the infestation index for I. ricinus larvae (0.236; 0.022). Based on the seroprevalence and prevalence of infested rodents, the level of potential risk for human and animal could be predicted.